Epin Plus and Epin-Extra - effective instruments for spring wheat - Nechaeva Eugenia M.; Dmitrevskaya Inna I. (BIO Web of Conferences, 2024)
A comparison experiment was done on the effective of the new organic-mineral fertilizer Epin Plus and the plant growth regulator Epin-Extra. Epin Plus contains: nitrogen, phosphorus, potassium, boron, fulic acids, 24-epibrassinolide. Epin-Extra contains 24-epibrassinolide. In the field experiment, spring wheat was grown for three years. During the growing season, the plants were sprayed with Epin-Extra and Epin Plus. Field experiment treatment includes: control, with the application of fertilizers and spraying of wheat during the growing season with Epin Plus in dose of 50 ml/ha, 70 ml/ha, 100 ml/ha, with spraying of plants with Epin-Extra at dose of 50 ml/ha. It was found that the maximum grain yield was recorded in the treatment with Epin Plus (70 ml/ha), which was 28.6% more than from control, 21.7% more than the treatment with fertilizer application, 12.2 % compared to the Epin-Extra treatment (50 ml/ha), 22% more than the Epin Plus treatment (50 ml/ha) and 20.2% more than the Epin Plus treatment (100 ml/ha). It was recorded in the control treatment grain protein was 12.9%, and in the Epin Plus treatment (70 ml/ha) – 15.8%. The gluten content of wheat grain in the Epin-Extra (50 ml/ha) and Epin Plus (70 ml/ha) treatment was 33.50 - 35.80%, in other treatment 30.5 - 31.95%.